EXPLORATION OF BURNOUT PHENOMENA AND COPING STRATEGIES FOR WORK-RELATED STRESS AMONG GENERATION Z - Ni Putu Shintania Pramesti; Luh Putu Mahyuni (RADJA PUBLIKA, 2026)
This study aims to explore the phenomenon of burnout and coping strategies in dealing with work stress among Generation Z (Gen Z) during the high season. This phenomenon arises due to the increasing workload, multiple tasks, and excessive working hours experienced by Gen Z workers. With the unique characteristics of Gen Z such as the need for work-life balance and sensitivity to mental health, this can trigger burnout. The study used a qualitative approach with an exploratory design. Data were collected through in-depth interviews with Gen Z workers, coworkers, and management, and supported by operational documentation. The results showed that work stress was triggered by organizational factors, such as increasing task demands, dual roles, time pressure, limited organizational structure, and interpersonal relationship dynamics. Continuous stressful conditions can lead to burnout, which is characterized by physical, emotional, and mental exhaustion, as well as low self-achievement. To deal with this pressure, Gen Z workers apply coping strategies such as social support, self-healing, and self- evaluation. These findings underscore the importance of organizations' role in creating a supportive and adaptive work environment to Gen Z characteristics to prevent work stress and burnout, particularly in the small to medium-scale tourism sector.